Hexagon-Twist Frequency Reconfigurable Antennas via Multi-Material Printed Thermo-Responsive Origami Structures - Zhang, Ya-Jing; Wang, Li-Chen; Song, Wei-Li; Chen, Mingji; Fang, Daining (Frontiers in Materials, 2020)
The origami structure has caused a great interest in the field of engineering, and it has fantastic applications in the deployable and reconfigurable structures. Owing to the unique multi-stable states, here a typical hexagon-twist origami structure is fabricated via multi-material printing technology. The printed structure has multi-stable features and the stiffness of the deformable structure is dramatically reduced under thermal triggering. Such behavior causes an increase in the structural degree of freedom, allowing for self-deployment via releasing the prestored energy in the elastic crease. The response time and reaction time of the self-deployment process are also studied and illustrate the higher energy barrier of the folded state, the longer self-deployment time. Utilizing such unique features and design principles, a prototype of frequency reconfigurable origami antenna of nine diverse operating modes is subsequently designed and assembled with the hexagon-twist origami structure as the dielectric substrate. The antenna implements the cross-band from two different frequency bands, enabling to realize frequency reconfigurable under thermal condition.